Isolation and identification of SiCOL5, which is involved in photoperiod response, based on the quantitative trait locus mapping of Setaria italica - Li, Fei-fei; Niu, Jia-hong; Yu, Xiao; Kong, Qing-hua; Wang, Run-feng; Qin, Ling; Chen, Er-ying; Yang, Yan-bing; Liu, Zhen-yu; Lang, Li-na; Zhang, Hua-wen; Wang, Hai-lian; et al. (Frontiers in Plant Science, 2022)
Foxtail millet (Setaria italica) is a versatile grain/fodder crop in the arid and the semi-arid regions, feeding malnourished people in some poverty-stricken areas of the world. Photoperiod sensitivity is one of the major constraints for the exchange of the foxtail millet germplasm resources. Also, foxtail millet can act as the model species for studying the photoperiod sensitivity of C4 crops. However, the genetic basis of photoperiod response of foxtail millet is still poorly understood. To detect the genetic basis of photoperiod sensitivity related traits, a recombinant inbred population (RIL) consisting of 313 lines was established by using a cross with a spring-sowing variety‘longgu 3’ and a summer-sowing variety‘canggu 3’. The RIL population was genotyped by using the whole-genome re-sequencing technique and was phenotyped in four environments. A high-density genetic linkage map of 639,093 SNP markers and 2076 bin markers was constructed, with an average distance of 0.69 cM between adjacent markers. A total of 21 QTLs were identified through composite interval mapping (CIM). A total of 19 photoperiod sensitivity related candidate genes were predicted according to the results of the gene annotation data. Further analysis showed that the candidate genes could be assigned to 9 gene families, among which genes, 11 genes were selected as the important candidate genes based on the gene annotation, SNP variation analysis between the parents, putative cis-element analyis and expression analysis. Then a putative candidate gene SiCOL5 was isolated based on QTL mapping analysis. Further research showed that the SiCOL5 is sensitive to photoperiod, and is regulated by biological rhythm related genes. The function analysis suggested that the SiCOL5 can positively regulates flowering time. Furthermore,Y2H and BiFC showed that the SiCOL5 can interacted with SiNF-YA1 in nucleus.